Revisiting Contact Electrification at Polymer-Liquid Interfaces - Tan, Chen (Langmuir : the ACS journal of surfaces and colloids, 2022)
Contact electrification (CE) occurs naturally at all interfaces between solids and solids, solids and liquids, solids and gasses, and so forth. It has been extensively studied for decades. While CE at a solid-solid interface has been demonstrated to be primarily caused by electron transfer, the underlying mechanism of CE at a liquid-solid interface remains controversial. In this paper, the CE process between polyethylene terephthalate (PET) and different inorganic solutions at different temperatures is studied to investigate the charge transfer mechanism. The observed temperature-CE charge relationship falls into two categories, that is, the general case and the special case. In the general case, the CE charge first increases negatively and then positively with the temperature. The CE charge increasing negatively could result from enhanced electron transfer at the interface, while the CE charge increasing positively may be caused by increasing adsorption of cations, which neutralize the negative charges on the PET surface. In contrast, the CE charge first increases positively and then negatively with the temperature in the special case. The CE charge increasing positively could be attributed to more cations being attracted to the negatively charged PET surface, while the charge increasing negatively may be caused by more anions being attracted to the PET due to enhanced cation adsorption. Supported by the surface charge and dynamic charge transfer at different PET-solution interfaces and solution temperatures, our study provides a plausible interpretation of the temperature-dependent CE at the polymer-liquid interfaces